Wireless power transfer for electric vehicle using an adaptive robot - Barzegaran, M. R.; Zargarzadeh, Hassan; Mohammed, O. A. (2016 IEEE Conference on Electromagnetic Field Computation (CEFC), 2016)
Charging time and power transfer efficiency are the main issues of wireless power transfer for electric vehicle. It is proposed in this paper to resolve both of the issues using the concept of transformer induction. An autonomous robot arm equipped with several sensors is mounted to the vehicles undercarriage to carry the receiving coil and locate it at the right place which is into the transmitting core during charge. In addition, silicon carbide MOSFETS are used in power converter to keep the frequency as high as possible to decrease the charging time. Through this method, the above issues and the problem of large non permeable air gap and accordingly electromagnetic interference are resolved. Also the charging time is decreased dramatically.